SURFACE STRUCTURE OF PROPERTIES ALLOY 36NHTU POST ION IMPLANTATION - Tujakbaev, B.T.; Ahmetzhanov, B.K.; Skakov, M.K. (Recent Contributions to Physics, 2008)
The articles are shown structure and properties of dispersion-hardening alloy 36NHTU implanted by ions Ti+, Ta+ and N+. It is established, that ionic implantation leads to formation of an implanted layer about 0,2¸0,3 micrometer. Implantation by ions of nitrogen leads to increase of cyclic resistance of an alloy. Ionic implantation Ti+, Ta+ allows to increase corrosion stability sharply.